2021
DOI: 10.1186/s12879-021-05902-5
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired bacteraemia in COVID-19 in comparison to influenza A and influenza B: a retrospective cohort study

Abstract: Background During the coronavirus disease 2019 (COVID-19) pandemic in the Netherlands it was noticed that very few blood cultures from COVID-19 patients turned positive with clinically relevant bacteria. This was particularly evident in comparison to the number of positive blood cultures during previous seasonal epidemics of influenza. This observation raised questions about the occurrence and causative microorganisms of bacteraemia in COVID-19 patients, especially in the perspective of the wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 28 publications
0
30
1
Order By: Relevance
“…9,10,[14][15][16][17][18]20,23,[27][28][29][30][31][32][33] , Streptococcus spp. 9,10,[15][16][17][18]20,23,27,29,34 , Escherichia coli 9,14,16,27,28,30,31,33,34 , Klebsiella spp. 9,10,12,15,16,18,22,24,27,28,31 , Enterococcus spp.…”
Section: Resultsmentioning
confidence: 99%
“…9,10,[14][15][16][17][18]20,23,[27][28][29][30][31][32][33] , Streptococcus spp. 9,10,[15][16][17][18]20,23,27,29,34 , Escherichia coli 9,14,16,27,28,30,31,33,34 , Klebsiella spp. 9,10,12,15,16,18,22,24,27,28,31 , Enterococcus spp.…”
Section: Resultsmentioning
confidence: 99%
“…The current meta-analysis is more comprehensive and included a total of 71 studies [2,80] and one abstract [3], including a total of 31,953 patients. The inclusion of 18 recently published studies [2,3,[5][6][7][8][9][10][12][13][14]22,24,27,41,62,64,65] contributed to the refinement of the estimate of the pooled prevalence of pathogens contributing to coinfections in SARS-CoV-2 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Of the initial 7317 retrieved publications, there were 4609 duplicate articles, and 2080 articles were found to be irrelevant based on their titles and abstracts and were excluded. An additional 1065 articles were excluded after review, meaning that we included 72 articles in the systematic review [80][81][82], while 68 articles were included in the meta-analysis [2][3][4][5][6][7][8][9][10][11][39][40][41][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][59][60][61][62][63][64][65][66][67][68][69][70][80][81][82] (Figure 1).…”
Section: Characteristics and Quality Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al showed that in a cohort of non-survivors of COVID-19, 50% had a secondary infection. 2 Current data on patients with COVID- 19 show…”
Section: Introductionmentioning
confidence: 99%